The processing, microstructure and creep properties of Pb-free solders for harsh environments - Godard Desmarest, S (2013)
The constitutive mechanical behaviour with a focus on creep of Sn-Pb and various Sn-Ag-Cu based Pb-free solders in the 25-150°C temperature range has been studied using nanoindentation and various new meso-scale tests. All alloys have been studied as bulk wave soldering bars, as-received solder balls and solder joints. Ball Grid Array (BGA) solder joints in a typical electronic configuration were manufactured in-house using both Cu and Pd-Ag metallizations. Microstructural characterisation of all configurations used various types of optical and electron microscopy and showed that the solder pad metallization type played a major role in intermetallic compound (IMC) formation. There were comparatively fine and coarse-grained microstructures in both as-received solder balls and BGA solder joints depending on ball diameter. Nanoindentation creep measurements in the stress range 20-500MPa showed that grain boundary sliding occurred together with dislocation glide and dislocation climb in the low temperature (25-50°C) and high temperature (100-150°C) regimes respectively. Smaller grain sizes (<20µm) encouraged grain boundary sliding that enhanced creep. New elevated temperature mechanical tests were developed using the nanoindentation platform to enable testing of entire solder joints in shear and compression, with stresses in the 1E-2 - 3MPa range, more relevant to in-service conditions than those in nanoindentation. Meso-scale spherical indentation creep behaviour in compression on as-reflowed solder balls showed good agreement with that obtained by conventional nanoindentation. However, when BGAs were tested in shear, the solder microstructure had relatively little influence on the creep response, which was significantly less creep resistant than individual phases in the ball obtained by nanoindentation or the ball itself obtained by meso-scale spherical indentation. In shear, the creep conformed to diffusion controlled behaviour and interfacial microstructure was suggested to now control creep response, with the microstructure of the majority of the solder joint playing only a minor role.